Perioperative glucocorticoid administration for prevention of systemic organ failure in patients undergoing esophageal resection for esophageal carcinoma - Raimondi, Antônio Marcos; Guimarães Jr., Hélio Penna; Amaral, José Luiz Gomes do; Leal, Patrícia Helena Rocha (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Preoperative glu- cocorticoid administration has been proposed for reducing postoperative morbidity. This is not widely used before esophageal resection because of incomplete knowledge regarding its effectiveness. The aim here was to assess the effects of preoperative glucocorticoid administra- tion in adults undergoing esophageal resection for esophageal carcinoma. SEARCH STRATEGY: Studies were identified by searching the Cochrane Controlled Trials Reg- ister, MEDLINE, EMBASE, Cancer Lit, SCIELO and Cochrane Library, and by manual searching from relevant articles. The last search for clinical trials for this systematic review was performed in December 2004. SELECTION CRITERIA: This review included randomized studies of patients with potentially resectable carcinomas of the esophagus that compared preoperative glucocorticoid adminis- tration with placebo. DATA COLLECTION AND ANALYSIS: Data were extracted by the same reviewers, and the trial quality was assessed using Jadad scoring. Relative risk and weighted mean difference with 95% confidence limits were used to assess the significance of the difference between the treatment arms. RESULTS: Four randomized trials involving 146 patients were found. There were no dif- ferences in postoperative mortality, sepsis, anastomotic leakage, hepatic and renal failure between the glucocorticoid and placebo groups. There were fewer postoperative respiratory complications (p = 0.005) and multiple post- operative complications (p = 0.004) and lower postoperative plasma interleukin-6 levels (p = 0.00001) with preoperative glucocorticoid ad- ministration. There was a higher postoperative PaO2/FiO2 ratio (p = 0.0001) with preoperative glucocorticoid administration. CONCLUSION: Prophylactic administration of glucocorticoids is associated with decreased postoperative complications.